2012
DOI: 10.1209/0295-5075/99/38002
|View full text |Cite
|
Sign up to set email alerts
|

Network evolution towards optimal dynamical performance

Abstract: Understanding the mutual interdependence between the behavior of dynamical processes on networks and the underlying topologies promises new insight for a large class of empirical networks. We present a generic approach to investigate this relationship which is applicable to a wide class of dynamics, namely to evolve networks using a performance measure based on the whole spectrum of the dynamics' time evolution operator. As an example, we consider the graph Laplacian describing diffusion processes, and we evol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 35 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…[1][2][3][4][5] To understand how these systems function one needs to determine the structure and rates in these networks. In recent years, significant experimental and theoretical advances in investigating mechanisms of complex chemical and biological systems have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] To understand how these systems function one needs to determine the structure and rates in these networks. In recent years, significant experimental and theoretical advances in investigating mechanisms of complex chemical and biological systems have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that networks can be reconstructed from their Laplacian spectra by evolutionary optimization [24,25]. Recently, network evolution was applied to generate networks which display subdiffusive dynamics [26]. Here, subdiffusion is specified by the average return probability of a random walker that decays more slowly than in normal diffusion.…”
mentioning
confidence: 99%
“…To elucidate how the spectral properties are encoded in the structure of the evolved networks, in the present work we apply the method of ref. [26] to regular networks, i.e., networks in which each vertex has the same number of neighbors. Two typical network configurations evolved towards a target spectral dimension of d s = 1.4 p-1 arXiv:1503.02446v2 [physics.soc-ph] 27 Aug 2015 are shown in fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Since the functioning of these complex systems is strongly influenced by their structures, the most important step in theoretical analysis is to determine the topology of underlying networks. Despite recent strong advances in understanding the dynamical and structural properties of complex chemical and biological networks, [6][7][8][9][10][11][12][13][14] revealing the hidden structures of networks and their relations to dynamics remains a challenging task.…”
Section: Introductionmentioning
confidence: 99%